INDEKS PEMBANGUNAN MANUSIA MEMODERASI PENGARUH KINERJA KAPASITAS FISKAL DAERAH DAN SILPA PADA DAYA SAING DAERAH - Mayun Narindra, A A Ngr; Ketut Jati, I (E-Jurnal Akuntansi, 2016)
The performance of the region fiscal capacity is Revenue Sharing Fund and SiLPA might not linearly impact the zone competitiveness because they are some contigency factors, which one of them is Human Development Index (H DI ). This study aims to discover the influence of region fiscal capacity performance to area competitiveness, also the ability of HDI to modernize the influence of region fiscal capacity performance for zone competitiveness. An examination with eight regencies and a city in Bali province within 2008-2013 period of study, were using quantitative and qualitative data with a secondary source from Financial Bureau of Bali province and Statistic Center. The data had been tasted and fulfilled the classical assumption testing; suitability model testing with adjusted R 2 =46%, afterwards the research of hypothesis testing has finally done by using Moderated Regression Analysis technique. The result of the test states that the region fiscal capacity performance is Revenue Sharing and Human Development Index, those two aspects give a positive and significant impact on zone competitiveness of regency or city in Bali province. Also, the HDI is capable to modernize the influance of Revenue Sharing Fund and SiLPA on Zone Competitiveness .
Keywords: Revenue Sharing Fund, SILPA, Human Development Index, Zone Competitiveness